Crystalline tetraatomic boron(0) species - Lu, Wei (2021)
Reaction of a 1,2-diboraallene 1 with tetradibromodiborane B2Br4 coordinated by a cyclic (alkyl)(amino)carbene (cAAC) in a 3:1 ratio affords a neutral tetraboron species 2 that possesses a planar tetraatomic boron(0) unit with the average oxidation state of zero. X-ray diffraction analysis and computational studies indicate that 2 features the delocalized electrons in the part of the σ-framework of the B4 unit, as well as the conjugated π-system over the C–B3–C moiety.